BISPHOSPHONATE-RELATED OSTEONECROSIS OF THE JAW A 3-YEARS RETROSPECTIVE STUDY OF FREQUENCY AND RISK FACTORS - Rosen Tsolov; Elena Firkova; Ivan Chenchev; Georgi Jordanov; Stefka Paecheva (Peytchinski Publishing, 2019)
Purpose: To estimate the frequency of bisphosphonate-related osteonecrosis (BRONJ) in the Bulgarian population between 2015-2018 and the correlation with the type of bisphosphonates as risk factors associated with BRONJ development. Materials and methods: A retrospective analysis of the official database from the national health insurance system was conducted. The total number of patients with developed BRONJ was estimated. The type of intravenous bisphosphonate administered was associated with the incidence of BRONJ. Results: 3543 patients developed BRONJ during 2015 - 2018. The frequency of the condition is constantly increasing. The incidence of BRONJ among patients receiving ibandronate acid was significantly higher than patients on alendronic acid treatment (p <0.001). Conclusions: BRONJ is constantly increasing condition in the Bulgarian population among cancer patients, treated with intravenous bisphosphonates. Administration of Ibandronic acid can be used as a significant risk factor and a predictor for BRONJ development in those patients.